Breaking bad habits defy industry norms and reinvigorate your business - Vermeulen, Freek (Harvard Business Review Press, 2017)
Every organization follows a set of best practices - ideas, processes, and philosophies that have become accepted in their respective industries. In many cases, best practices are a good thing: they allow organizations to operate more quickly and efficiently. But, even though they're created and then followed with good intentions, best practices can also have pernicious effects. In the UK, for example, the government ranked IVF clinics based on their success rates, and made the rankings public. On the surface, this seems like a good thing. The government, in an effort to be more transparent, was hoping to provide patients as much information as possible. The problem is that the rankings changed the behavior of a lot of clinics, mostly in negative ways. With the rankings in mind, clinic administrators sought patients with a high-probability of getting pregnant in order to goose their success rates and climb higher in the rankings. In the end, the best practice led to bad incentives and misinformed patients. In Breaking Bad Habits, Freek Vermeulen explains the hidden dangers of best practices, how to identify the bad from the good, and how to protect oneself in the future. Most important, he also offers a path toward competitive advantage: once companies weed out their worse practices, they can transform their previous inefficiencies into new sources of innovation.--
Keywords: Organizational change / Management; Methods engineering; Experiential learning; Creative ability in business; Industrial management